Body build of children and youth with cerebral palsy - Łuczak, Ewa; Mięsowicz, Irmina; Szczygieł, Andrzej (Polskie Towarzystwo Antropologiczne, 1998)
The material consists of the results of anthropometric measurements of 16 somatic traits o f 155 children and youth (83 boys and 72 girls) at the age of 7-18 years. The analysis of 2-score values showed that the low body height, narrow hips, laterally flattened chest and low body mass, in spite of slight differences make boys and girls with cerebral palsy more similar to one another with respect to body proportions than to their healthy peers.